Drive : the surprising truth about what motivates us - Pink, Daniel H. (New York, NY : Riverhead Books, 2009)
Pink argues that the secret to high performance and satisfaction in today's world is the deeply human need to direct our own lives, to learn and create new things, and to do better by ourselves and our world.
Includes bibliographical references (p. [221]-229) and index.
Keywords: Motivation (Psychology)